Can global aquaculture growth help to conserve wild fish stocks? Theory and empirical analysis - Christian W. J. Bogmans; Daan van Soest; C. Cahu (John Wiley & Sons Ltd, 2025)
Can fed aquaculture growth alleviate overfishing and foster the conservation of wild fish stocks? To examine this question we present a stylized fishery model of trade in edible fish and fishmeal that incorporates both market linkages and biological (predator–prey) linkages between the aquaculture sector and capture fisheries. We study the effects of local aquaculture growth, as induced by an increase in aquaculture feedefficiency (technology shock), and of external or global aquaculture growth as experienced by either a drop in the price of edible fish or as an increase in the price of fishmeal (price shocks). While domestic (or “local”) aquaculture growth increases wild fish stocks due to positive market interactions, the effects of external (or “global”) aquaculture growth are generally ambiguous and depend on the strength of biological linkages. A stylized empirical application of the cod (predator) and capelin (prey) fisheries in the Barents Sea illustrates that the biological linkages between cod and capelin reduce the positive impact of aquaculture on cod conservation roughly by 50%. Recommendations for Resource Managers: • Fishery managers should differentiate between the effects of local, technology‐driven aquaculture growth and the effects of global, price‐driven aquaculture growth. The latter may have negative impacts on local fish stocks and the economy. • Real fishmeal prices increased substantially since the year 2000. For multispecies fisheries that are not properly managed, this can increase pressure on fish stocks if predator–prey linkages are strong, if prey species regeneration is slow, and if pelagic prey species are relatively easy to catch. • An empirical application shows that predator–prey linkages reduce but not overthrow the positive effects of global aquaculture growth on the conservation of local predator fish stocks. This provides some evidence that a reallocation of fishing effort from higher to lower trophic levels can conserve fish stocks at higher trophic levels.